PENGARUH INCOME LEVEL DAN EDUCATION LEVEL TER-HADAP BEHAVIORAL INTENTION TO OWN CREDIT CARD DENGAN DIMEDIASI PERCEIVED FINANCIAL COST DAN PER-CEIVED SELF EFFICACY PADA BANK BCA DI SURABAYA - Prathama, Gibson; Harsono, Soni (Universitas Lambung Mangkurat, 2023)
Credit cards are becoming a trend among the people of Surabaya to have them with vari-ous consequences that must be accepted. Even its use has increased post-covid-19. Of course, individuals who had it had to consider their income and qualified knowledge regarding credit cards. This study seeked to reveal the role of income level and education level on behavioral intention to own a credit card of BCA in Surabaya mediated by per-ceived financial cost and perceived self-efficacy using a quantitative method using Struc-tural Equation Modeling (SEM) with a total sample of 190 respondents from customers who own credit cards of BCA Bank in Surabaya. The results showed that income level and education level had an effect on perceived financial cost. Income level, education level, perceived financial cost, and perceived self-efficacy had an effect on behavioral intention to own. Income level and education level had an effect on behavioral intention to own through perceived financial cost, and income level and education level influenced behavioral intention to own through perceived self-efficacy. Suggestions for research need to broaden the scope was not only in Surabaya and the Bank needed to pay attention to income levels and customers' understanding of BCA credit cards.